Analisis Motivasi dan Kemandirian Belajar Calon Guru Fisika dalam Eksperimen Fisika Dasar Berbasis Laboratorium Virtual - Nurlina Nurlina; Aulia Rahmadhani; Irsan Rahman; Arie Arma Arsyad; Ummu Kalsum (Postgraduate, University of Mataram, 2025)
Virtual laboratories have emerged as innovative solutions in education, particularly in overcoming the limitations of physical laboratory infrastructure. In prospective physics teacher education, understanding how virtual laboratories influence motivation and self-regulated learning is crucial. This study aims to describe the motivation and self-regulated learning among prospective physics teachers participating in virtual laboratory-based fundamental physics experiments. A descriptive quantitative approach was employed, involving 27 prospective physics teachers at the Universitas Sulawesi Barat. Data were collected using a questionnaire adapted from the Motivated Strategies for Learning Questionnaire (MSLQ). Results show that all items scored within the high category, with mean values ranging from 3.65 to 4.34 on a 5-point Likert scale, indicating generally high levels of motivation and self-regulated learning. However, one item (A5) indicated a relatively lower mean score, suggesting that some participants may be more extrinsically than intrinsically motivated. Additionally, most respondents perceived the virtual laboratory as moderately to highly helpful in understanding physics concepts. This study contributes to the development of technology-based learning strategies and emphasizes the importance of designing learning experiences that strengthen prospective teachers’ self-belief. Further research should employ qualitative methods to explore the deeper learning experience of prospective physics teachers in virtual laboratories